2011
DOI: 10.1111/j.1751-1097.2011.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy with Pc 4 Induces Apoptosis of Candida albicans

Abstract: The high prevalence of drug resistance necessitates the development of novel antifungal agents against infections caused by opportunistic fungal pathogens such as Candida albicans. Elucidation of apoptosis in yeast-like fungi may provide a basis for future therapies. In mammalian cells, photodynamic therapy (PDT) has been demonstrated to generate reactive oxygen species, leading to immediate oxidative modifications of biological molecules and resulting in apoptotic cell death. In this report, we assess the in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 36 publications
2
33
0
3
Order By: Relevance
“…In addition, the Pc 4 fluorescence appears to be site specific, which is consistent with previous studies which showed that Pc 4 preferentially binds to intracellular organelles once the cellular uptake has occurred (31,39). To examine whether the mitochondrion is one of the organelles to which Pc 4 binds, we coloaded the Pc 4-treated microconidia and hyphae with a commercially available mitochondrion-specific probe.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In addition, the Pc 4 fluorescence appears to be site specific, which is consistent with previous studies which showed that Pc 4 preferentially binds to intracellular organelles once the cellular uptake has occurred (31,39). To examine whether the mitochondrion is one of the organelles to which Pc 4 binds, we coloaded the Pc 4-treated microconidia and hyphae with a commercially available mitochondrion-specific probe.…”
Section: Discussionsupporting
confidence: 61%
“…Within 5 h following irradiation of Pc 4-treated microconidia and hyphae, their metabolic activities were assayed using the colorless sodium salt of XTT (2,3-bis[2-methoxy-4-nitro-5-sulfophenyl]-2H-tetrazolium-5-carboxyanilide inner salt) (Sigma-Aldrich, St. Louis, MO), which is converted by mitochondrial dehydrogenases of viable microconidia/hyphae into a water-soluble orange formazan derivative through the reduction of the tetrazolium ring of XTT. The absorbance of the resulting orange solution was measured using a spectrophotometer (Spectronic Genesys 5; Analytical Instruments, Golden Valley, MN) at a wavelength of 492 nm as previously described (30,31). Note again that some microconidia may have become hyphal during the overnight Pc 4 incubation in complete medium.…”
Section: Methodsmentioning
confidence: 99%
“…The light therapeutic properties studies with antimicrobial purpose are primarily motivated by resistance cases of conventional antimicrobial 3,6,[11][12][13][14] . The need to overcome these deficiencies led to the exploration of Petri dishes containing Agar Sabouraud Dextrose culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…The most important factor governing the PDT results is how the FS interacts with the cells in the tissue or target lesion, and the key aspect of this interaction is related to the FS intracellular location. The incubation time is required to allow the drug to be absorbed by the microorganism and accumulate in the cell structures 20 , such as mitochondria, lysosomes, endoplasmic reticulum, Golgi apparatus and plasma membrane 3 . During irradiation, it is necessary that FS is already located inside the cell, because the singlet oxygen, formed after light application, presents minimal diffusion (100nm) and cytotoxic effect only in the place where it is produced 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous published studies have shown PDT to be highly effective in the in vitro inactivation of fungi (19,20,31). In addition, it is considered that the development of resistance to PDT by microbes is an unlikely event, because PDT is typically a multitarget process, which is a difference between PDT and most other antifungal drugs (22).…”
mentioning
confidence: 99%